Advances in Carbon Materials for Sodium and Potassium Storage. (16th June 2022) - Liu, Mingquan; Wang, Yahui; Wu, Feng; Bai, Ying; Li, Ying; Gong, Yuteng; Feng, Xin; Li, Yu; Wang, Xinran; Wu, Chuan
Abstract: Over the past decades, ground‐breaking techniques and transformative progress have been achieved on exploring alternative battery candidates beyond lithium‐ion batteries, among which sodium‐/potassium‐ion batteries (SIBs/PIBs) are receiving rapidly increased attention. Great efforts have been devoted to developing verified anode materials. Carbon materials take the leading position because of their abundance, low‐cost, environmental friendless, and commercial potential. While it is easy to understand which specific carbon material exhibits outstanding performance, the understanding of electrochemical reaction mechanisms, the structure–performance relation, and the interfacial properties of carbon anodes are rather difficult. It is urgently required to comprehensively summarize and further compare these fundamental issues, but it is still insufficient. This review concentrates on recent progress of carbon materials for SIBs and PIBs, and at the beginning summarizes the fabrication and characterization of different carbon allotropes, then fundamentally compares the ion storage mechanisms and interfacial chemistries. Furthermore, the relationship between the mechanism‐oriented and interface‐correlated performance and material optimization strategies is established. Finally, critical challenges and future developments of carbon anodes for the practical realization of SIBs/PIBs are proposed. This review gives a comprehensive summary and perspective from mechanisms to material design, offering a reliable guidance of carbon materials for SIBs and PIBs. Abstract : Carbon materials hold promisingly commercial potential as anodes for sodium and potassium ion batteries. Herein, a comprehensive and comparative review of the advances on carbon materials for sodium and potassium storage is summarized and compared, containing fabrication, storage mechanism, interfacial chemistry, the material optimization strategies, and the challenges and prospects.